Structural and Cultural Reforms In The Indonesian Bureaucracy - Marjoni Rachman; Marsuq Marsuq (Journal La Bisecoman, 2023)
Bureaucratic reforms carried out in Indonesia at present has five main goals and objectives, namely a cleanbureaucracy, bureaucracy is efficient, transparent bureaucracy, bureaucracy that serves well as a decentralizedbureaucracy. The five targets and objectives are more directed at the implementation of structural reforms in the bureaucracy, but bureaucracy is a form and order which contains the structure and culture. Structure refers to thearrangement of a temporary order that contains the value of culture, systems, and custom made ​​by the principals that reflect the behavior of human resources. Therefore, institutional reform of the bureaucracy including the composition of agovernment bureaucracy, as well as the values ​​of reform, governance systems and procedures of the behavior of human resources. In connection with the reform of the bureaucracy that should be done with reference to the two aspects are equally important, namely the institutional aspects that lead to the reform of its structure, levels of hierarchy andmanagement system; and reform of aspects of culture, namely rearranging organizational culture that had been executed.